Persistent mullerian duct syndrome presenting as retractile testis with hypospadias: A rare entity - Vanikar, Aruna V (World J Clin Cases, 2016)
A rare entity of persistent mullerian duct syndrome usually presents with a common symptom of undescended testis (UDT) or hernia. Male pseudo-hermaphroditism with persistent internal mullerian duct structures can present with a 46, XY karyotype with normal external genitalia and. It arises due to deficiency of anti-mullerian substance, resulting from reduced production/responsiveness to mullerian duct, leading to persistence of mullerian duct along with normal development of Wolffian duct structures. Presence of mullerian structure prevents testicular descent increasing the risk of testicular vanishing syndrome. The authors here report a case of 16 years old phenotypical male who came with retractile right sided testis and left side UDT in the urology out-patient department. Explorative laparotomy was performed and an ill-defined mass was excised and sent for histopathological examination. Histopathology revealed presence of mullerian structures. The serum testosterone level was normal, buccal smear cytology and karyotyping revealed a 46, XY genotype of the patient.